Nuchal cord at delivery and perinatal outcomes: Single-center retrospective study, with emphasis on fetal acid-base balance - Rohitkumar Vasa; Roger Dimitrov; Shivani Patel (Elsevier, 2018)
Aim: Our study objectives were to evaluate umbilical cord blood acid-base balance in presence of nuchal cord at delivery, effects of nuchal cord at delivery on perinatal outcomes and incidence of nuchal cord in a racially diverse population. Methods: Perinatal records of 2530 women (predominantly African American and Hispanic) who delivered in 2012 were examined. Perinatal outcomes of women who delivered a baby with nuchal cord were compared with those without nuchal cord. Results: In this study, incidence of nuchal cord was 23.5% and incidence of tight nuchal cord was 1.9%; 4.2% of babies with nuchal cord required resuscitation and 3.2% of babies with nuchal cord needed to be admitted to NICU. In our study, 4.2% of babies with nuchal cord required resuscitation and in total 3.2% of babies with nuchal cord needed to be admitted to NICU. Nuchal cord frequency increased from 15.6% at ≤36 weeks to 22.8% at ≥37 weeks. Significantly elevated umbilical cord Veno-Arterial pH differential was noted in babies with nuchal cord, indicating fetal acidemia. Conclusions: Perinatal outcomes of pregnancies with nuchal cord in predominantly African American and Hispanic women were not adversely affected. Analysis of umbilical cord blood gases suggests mixed respiratory and metabolic fetal acidosis. Key Words: nuchal cord, perinatal outcomes, umbilical cord blood gases